Holographic and heuristic education (Revista Electrónica Calidad en la Educación Superior, 2018)
This manuscript is a critique about the quality of education. Contains an integral proposal. A synthesis that obstacles to achieve a quality educational process, and the possible causes that are needed in the country. By comparing three countries (Finland, Singapore and Canada) with the Costa Rican model, the changes in the system are clarified, from the person as an individual, to society. Education is a natural process that is not enclosed in an enclosure, is in all spaces and times to build and deconstruct knowledge, from all possible views.